2011
DOI: 10.1016/j.adolescence.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward political engagement and willingness to participate in politics: Trajectories throughout adolescence

Abstract: Drawing on data from a longitudinal cohort‐sequential project, the present study examined developmental trajectories of adolescents’ attitudes toward political engagement and their willingness to participate in politics from grade 7 to 11 while accounting for the influence of school track and gender. Moreover, stabilities on the dependent variables were assessed. The results revealed differential trajectories regarding adolescents’ educational level. Increases were mainly shown for students attending the colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 39 publications
5
97
0
8
Order By: Relevance
“…Finally, previous studies have shown that educational level is related to adolescents' democratic views (Eckstein, Noack, and Gniewosz 2012;Flanagan et al 2005;Schulz et al 2010). The findings of our study partly contradict this finding.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, previous studies have shown that educational level is related to adolescents' democratic views (Eckstein, Noack, and Gniewosz 2012;Flanagan et al 2005;Schulz et al 2010). The findings of our study partly contradict this finding.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…With regard to educational track, students in college-bound tracks are often more positively oriented towards democracy, possess more comprehension of democracy, and have a better understanding of democratic institutions (such as parliament, constitution, and presidency) than those in vocational tracks (Eckstein, Noack, and Gniewosz 2012;Flanagan et al 2005;Schulz et al 2010). It is therefore relevant to take educational track and the related differences in social-economic and social-cultural background (OECD 2014) into account when studying adolescents' views on democratic decision-making.…”
Section: Orientations Towards Democracy and Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Janmaat (2011) zkoumal, zda jsou občanské kompetence mladých lidí provázány se sociálním a etnickým složením třídy, a zjistil, že rozdíly mezi úrovní občanských kompetencí jsou relativně větší v systémech charakterizovaných ranou selekcí na základě schopností. Eckstein et al (2012) zjistili, že postoje studentů z akademických větví se v čase zlepšovaly, zatímco postoje studentů nižších větví studia zůstávaly stabilní. Tento trend nebyl v našich datech pozorován.…”
Section: Rozdíly V Postojích žáKů Jednotlivých Typů šKol a V Postojícunclassified
“…There has been research that explores the effect of tracking on CPE in continental Europe, where single-country studies have been carried out in Israel (Ichilov 2002), Belgium (Stevens 2002), the Netherlands (Ten Dam and Volman 2003), Sweden (Persson and Oscarsson 2010;Persson 2012) and Germany (Eckstein, Noack, and Gniewosz 2012). Our study comprises three countries: Denmark, England and Germany.…”
Section: Introductionmentioning
confidence: 99%